Effect of the recombinant amelogenin peptide TRAP on remineralization of early enamel caries: an in-situ study - Qinghua Bai; Yaru Li; Mingzhu Wen; Dandan Ma; Yiwei Li; Jinpu Chu (BMC Oral Health)
Abstract Background The tyrosine-rich amelogenin peptide (TRAP) is the main enzymatic hydrolysis product of amelogenin during enamel development. The TRAP peptide has been shown to promote the remineralization of early enamel caries in vitro. The aim of this crossover blinded and randomized study was to evaluate the impact of recombinant amelogenin peptide TRAP on the remineralization of initial enamel caries lesions in situ. Methods The binding capacity of recombinant amelogenin peptide TRAP to hydroxyapatite (HA) and a demineralized enamel surface was analyzed by a Langmuir adsorption isotherm experiment and confocal laser scanning microscopy (CLSM). Subsequently, the remineralization effect of recombinant amelogenin peptide TRAP on initial enamel carious lesions was studied using an in situ caries model. In this randomized, crossover, and blinded study, 12 volunteers wearing intraoral removable in-situ appliances with one bovine enamel block were divided into three groups: Group A received deionized water (DDW, negative control); Group B received recombinant amelogenin peptide TRAP (100 µg/ml); Group C received sodium fluoride (2 ppm). The study took place over three periods of 14 days each. At the end of each treatment period, the percentage of surface microhardness recovery (%SHR) and the integrated change in subsurface hardness (%ΔIHC) were evaluated. Results Recombinant amelogenin peptide TRAP adsorbed onto HA and demineralized enamel surfaces. After in situ analysis, all samples hardened significantly compared with baseline. Fluoride had a significantly greater effect than all other treatments. %SMHR was significantly greater than the DDW for the recombinant amelogenin peptide TRAP. Considering subsurface remineralization, treatment with recombinant amelogenin peptide TRAP and fluoride promoted increases of 6.73% and 15.68%, respectively, in %ΔIHC compared with DDW. Conclusion Recombinant amelogenin peptide TRAP can promote the remineralization of early enamel caries lesions in situ. Clinical relevance This study demonstrated the potential of recombinant amelogenin peptide TRAP to assist in the remineralization of artificial carious lesions in situ. The amelogenin peptide TRAP may be a promising, non-fluorinated, biomimetic, remineralization anti-caries agent. Clinical trial number Not applicable.